Impact of mitochondrial damage on tumor microenvironment and immune response: a comprehensive bibliometric analysis - Xing, Yichun; Huang, Yi; Tang, Zhicheng; Lin, Ying; Zou, Yitong; Huang, Yaqiang; He, Zhaohui; Huang, Qunxiong; Wu, Jieying (Frontiers in Immunology, 2024)
Background: Mitochondrial damage contributes to apoptosis, oxidative stress, and inflammation, which collectively impact the immune system's function and the tumor microenvironment (TME). These processes, in turn, influence tumor cell growth, migration, and response to treatment.Objective: We conducted a bibliometric analysis to elucidate the complex interactions between mitochondrial damage, the immune system, and the TME.Methods: Data were sourced from the Science Citation Index Core Collection (WoSCC) and analyzed using advanced tools like VOSviewer and Citespace. Our focus was on literature published between 1999 and 2023 concerning the interactions between mitochondrial damage and the TME, as well as immune responses to tumors. The analysis included regional contributions, journal influence, institutional collaborations, authorship, co-cited authors, and keyword citation bursts.Results: Our research encompassed 2,039 publications, revealing an increasing trend in annual output exploring the relationship between mitochondrial damage, TME dynamics, and immune responses. China, the United States, and South Korea emerged as the leading contributors. Prominent